2022
DOI: 10.3847/1538-4357/ac887f
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Study of Blazar Broad Emission Line: Changing-look Blazars and the Baldwin Effect

Abstract: It is known that the blazar jet emissions are dominated by nonthermal radiation, while the accretion disk jets are normally dominated by thermal emission. In this work, our aim is to study the connection between the two types of emission by investigating the correlation between the blazar emission-line intensity property, which embodies the nature of an accretion disk, and the γ-ray flux property, which is the representative of jet emission. We compiled a sample of 656 blazars with available emission-line equi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…In addition, for the EC process in FSRQs, we consider the external photons from the DT for those highsynchrotron-peaked blazars (HSPs) and the external photons originating from the BLR for those low-synchrotron-peaked blazars (LSPs) and intermediate-synchrotron-peaked blazars (ISPs). In this case, we have 754 FSRQs using the model of external soft photons coming from the BLR; this is consistent with the assumption of a soft photon origin for FSRQs in the literature (e.g., Tan et al 2020) and also consistent with the facts that the FSRQs show significant broad emission lines and the emission lines contribute to the EC component significantly (Xiao et al 2022a). The rest of the five FSRQs are considered as HSPs, and the HSPs are naturally considered as TeV candidates (Zhu et al 2023).…”
Section: The Magnetic Field and The Lorentz Factor Of Electronssupporting
confidence: 89%
“…In addition, for the EC process in FSRQs, we consider the external photons from the DT for those highsynchrotron-peaked blazars (HSPs) and the external photons originating from the BLR for those low-synchrotron-peaked blazars (LSPs) and intermediate-synchrotron-peaked blazars (ISPs). In this case, we have 754 FSRQs using the model of external soft photons coming from the BLR; this is consistent with the assumption of a soft photon origin for FSRQs in the literature (e.g., Tan et al 2020) and also consistent with the facts that the FSRQs show significant broad emission lines and the emission lines contribute to the EC component significantly (Xiao et al 2022a). The rest of the five FSRQs are considered as HSPs, and the HSPs are naturally considered as TeV candidates (Zhu et al 2023).…”
Section: The Magnetic Field and The Lorentz Factor Of Electronssupporting
confidence: 89%
“…Lognormal distribution will typically be visible in the PDF of X-ray binaries with the accretion disk emission dominating them (Gandhi 2009). The accretion disk and the jet radiation may have significant connections (Ricci et al 2022;Zhang et al 2022;Xiao et al 2022). The accretion disk's instability caused turbulence disturbance to emerge at random in various radii.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the sources may be transition objects between BL Lacs and FSRQs. Xiao et al (2022a) reported their EWs as follows: EW Mg II = 8.31 ± 9.69 and EW C IV = 10.43 ± 2.51 for B3 0920+416, EW Mg II = 9.03 ± 3.78 for TXS 0106+612, EW Mg II = 13.61 ± 11.97 for S5 1044+71, EW Mg II = 40.89 ± 7.5 for B2 0218+35, EW Mg II = 93.59 ± 20.41 for PMN J0641−0320, and EW Mg II = 153.54 ± 7.3 for PKS 1758−651. In addition, we also fitted one SDSS spectrum (B3 0920+416; see Figure 2(a)), and we got EW Mg II = 7.4 ± 2.2 and EW C IV = 7.8 ± 2.1 for B3 0920+416.…”
Section: The Doppler Factormentioning
confidence: 99%
“…We thought that the six sources are similar to the changinglook AGNs (CL AGNs), which have recently attracted the attention of many astronomers. CL AGNs can exhibit a transition from Type 1 to Type 1.8, 1.9, and 2 or vice versa, featuring disappearing or emerging broad emission lines on timescales of months to years (LaMassa et al 2015;MacLeod et al 2016;Gezari et al 2017;Sheng et al 2020;Peña-Herazo et al 2021;Xiao et al 2022a). In particular, Cohen et al (1986) found that Mrk 1018 transitioned from Seyfert 1.9 to Seyfert 1 and then back to Seyfert 1.9 (McElroy et al 2016).…”
Section: The Doppler Factormentioning
confidence: 99%